2020
DOI: 10.35516/jjas.v16i1.55
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Growth, Biochemical Responses, and Ion Uptake in Paronychia Argentea Micro Plants Grown in Vitro under Salinity Induced Environment

Abstract: Paronychia argentea is a wild medicinal herbaceous herb that contains many secondary metabolites. It grows wild in Jordan under harsh high salinity soil conditions. This study was conducted to investigate the effect of salinity stress on growth, biochemical responses, and ion uptake of in vitro Paronychia argentea micro plants. Our results revealed a clear reduction in all growth parameters in response to an increase in salinity level used (0, 25, 50, 100, 200 mM). When the growth medium was supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
2
0
0
Order By: Relevance
“…Total soluble protein content in 24-epiBL non-pretreated shoots was induced at a low NaCl concentration (20 mM NaCl), but this parameter decreased with increasing NaCl stress. Amini & Ehsanpour (2006), Shibli et al (2007), Mohamed et al (2011) andAbu-Khadejeh et al (2011) reported that protein content in tomato decreased under salt stress, similar to our study findings. The decrease in the protein content under NaCl stress might be due to protein degredation, denaturation, proteolysis, decreases in the protein synthesis and free amino acids (El-Mashad & Mohamed 2012).…”
Section: Soluble Protein Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…Total soluble protein content in 24-epiBL non-pretreated shoots was induced at a low NaCl concentration (20 mM NaCl), but this parameter decreased with increasing NaCl stress. Amini & Ehsanpour (2006), Shibli et al (2007), Mohamed et al (2011) andAbu-Khadejeh et al (2011) reported that protein content in tomato decreased under salt stress, similar to our study findings. The decrease in the protein content under NaCl stress might be due to protein degredation, denaturation, proteolysis, decreases in the protein synthesis and free amino acids (El-Mashad & Mohamed 2012).…”
Section: Soluble Protein Contentsupporting
confidence: 92%
“…Since tomato plants are considered moderately tolerant to salt stress, 80 mM and 100 mM NaCl concentrations caused a dramatic decrease in developmental parameters for the M-28 hybrid cultivar we used for our study. Similar results related to development of shoots and roots of plantlets were also obtained in different works (Mercado et al 2000;Shibli et al 2007;Abu-Khadejeh et al 2011;Srinieng et al 2015;Khaliluev et al 2022). Roşca et al ( 2023) stated that reducing plant development under salt conditions may be an adaptive morphological strategy to limit water loss through transpiration.…”
Section: Length Fresh Weight and Dry Weight Of Shootssupporting
confidence: 77%